Assessment of Moroccan consumer preferences and purchasing behaviors related to meat and fish products - Chaymae Ghaffouli; Khaoula Faiz; Adil Roukbani; Bouchra Louasté (Discover Food)
Abstract Nowadays, there are several factors shaping consumers’ attitudes and consumption habits towards processed meat and fish products in many countries including Morocco. This study focuses on the assessment of Moroccan consumers’ behaviors and preferences towards processed meat and fish products. In this study, an online survey was conducted involving 1003 Moroccan consumers. The findings suggest that the consumption habits, or lack thereof, of processed meat and fish products among Moroccan individuals is associated with a range of factors, including economic considerations, health concerns, and the consumers’ sociodemographic characteristics. The data revealed that a majority of Moroccan consumers were ready to purchase meat and fish products with added natural preservatives for the shelf life extension, with only 17.3% of respondents less likely to purchase it. Growing consumer attentiveness in natural preservatives for shelf-life prolongation could improve their satisfaction.